2019
DOI: 10.1016/j.euroneuro.2018.11.1106
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dietary changes in n-6/n-3 polyunsaturated fatty acid ratios cause developmental delay and reduce social interest in mice

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…Noteworthily, a recent publication demonstrated social deficits when shifting the dietary fatty acid composition, specifically the ratio between ω-3- and ω-6-containing fatty acids, in mice [54]. We have shown previously that, in the murine brain, ether lipid deficiency is mainly compensated by increased levels of ω-6-containing phosphatidylethanolamine species, thus shifting the ω-3/ ω-6 balance in the abundant group of ethanolamine phospholipids [55].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthily, a recent publication demonstrated social deficits when shifting the dietary fatty acid composition, specifically the ratio between ω-3- and ω-6-containing fatty acids, in mice [54]. We have shown previously that, in the murine brain, ether lipid deficiency is mainly compensated by increased levels of ω-6-containing phosphatidylethanolamine species, thus shifting the ω-3/ ω-6 balance in the abundant group of ethanolamine phospholipids [55].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in environmental exposure models for ASD in rodents, n-3 PUFA or DHA supplementation were effective in reversing impairments in social interactions and elevation in social anxiety induced by maternal immune activation or exposure of food allergen during development [63,80,81]. Similarly, genetic models of ASD, including BTBR and serotonin transporter (SERT) knockout, demonstrated that pre-and postnatal n-3 PUFA or DHA supplementation may increase social interest and social preference for novel mice over objects as compared to mice fed n-3 PUFA deprived diets [82,83]. The improvements in social behaviors were observed in conjunction with higher DHA composition in the brain [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, genetic models of ASD, including BTBR and serotonin transporter (SERT) knockout, demonstrated that pre-and postnatal n-3 PUFA or DHA supplementation may increase social interest and social preference for novel mice over objects as compared to mice fed n-3 PUFA deprived diets [82,83]. The improvements in social behaviors were observed in conjunction with higher DHA composition in the brain [82][83][84]. Therefore, dietary DHA intervention shows promising results for the prevention of the core behaviors associated with ASD in different animal models.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of ASD, in which animals are prenatally exposed to valproic acid, n-3 supplementation with both α- and γ-linolenic acid protected against the development of autistic-like features [ 296 ]. Besides, in an inbred mouse model of ASD (BTBR mouse strain), dietary deficiency in n-3 PUFAs from gestation to early adulthood induced developmental delay and altered sociability [ 297 ]. These results were also observed when these animals were fed with dietary n-3 PUFAs supplementation [ 297 ], suggesting that LC n-3 PUFAs cannot counterbalance the social deficits induced by such a genetic inbreeding.…”
Section: Role Of Pufas In Neurodevelopmental Diseasesmentioning
confidence: 99%